Analysis and Design of a Flyback Converter for Universal Input and Wide Load Ranges - Gokcegoz, Ferudun; Akboy, Erdem; Obdan, A. Hulya (ISTANBUL UNIV-CERRAHPASA, 2021)
Flyback converts exhibit the advantages of simple structure, low cost, small volume, isolation, and control simplicity. However, flyback converters demonstrate disadvantages like leakage inductance; hence, losses are incurred. Losses pertain to the requirement of an external cooling system and external costs. It also results in low efficiency and the use of flyback converters in low power applications. The continuous conduction mode (DCM) is used for low power applications to achieve efficiency. In flyback converters, the reverse recovery losses of the diode are eliminated with DCM. There are many applications of flyback converter in industrial systems, such as led drivers, battery charge systems, telecommunication systems. In this study, analysis and design of a flyback converter for universal input and wide load ranges was performed. The detailed theoretical analysis was converters.
Keywords: DC-DC converter; flyback converter; wide load range; POWER-FACTOR; SNUBBER; Engineering